Thermal properties of PEG-based form-stable Phase Change Materials (PCMs) incorporated in mortars for energy efficiency of buildings - Sarcinella, Antonella (2023)
The purpose of a phase change material (PCM) is to store/release energy during its transition from solid to liquid state, being able to count on a range of melting/crystallization temperatures comparable to environmental temperatures. The inclusion of a PCM in mortars, or in other construction elements, guarantees a reduction in energy consumption for heating and cooling of buildings, provided that the phase transition range of the PCM corresponds to the variation range of the environmental temperatures. This implies that a PCM with a suitable transition range must be identified for each climate zone. Two Poly-Ethylene Glycol (PEG)-based form-stable PCMs have been, then, produced with the intent of include them in mortars applied in buildings located in different climatic zones, i.e. continental and Mediterranean regions. The form-stable PCMs were realized starting from two PEGs possessing different molecular weights, i.e. PEG800 and PEG1000, characterized by different ranges of melting/crystallization temperatures. The PEGs were included in flakes of a porous stone, i.e., Lecce Stone (LS), to produce two form-stable PCMs, namely: LS/PEG800 and LS/PEG800_PEG1000 (50/50 wt%). In the present paper, the thermal performance of the PCM-modified mortars was assessed in a climatic chamber able to simulate the variation of environmental temperatures in the two climatic zones under consideration. The effectiveness of the original PCMs to mitigate indoor temperature fluctuations was, then, assessed: it was found that the mortar formulations containing the mixed PCM (i.e., LS/PEG800_PEG1000 compound) offered the best advantage in reducing cooling and heating needs by 8 % and 13 %, respectively. On the basis of these results, the energy savings for indoor heating/cooling were calculated, with the corresponding reduction in costs: the inclusion of PCM LS/PEG800_PEG1000 in the mortars, especially those based on hydraulic lime, produced a noticeable reduction in the cooling cost, i.e. around 8 % during the summer, and 12 % during the spring and autumn seasons for internal heating of buildings located in the Mediterranean area. The time lag between the maximum and minimum temperatures with respect to the external (which simulates the environmental one) temperature was also evaluated: the cement-based mortar containing the mixed PCM generally performed the best, regardless of the climatic zone taken as a reference.